Imperfect certification and eco-labelling of products. Issue 3 (17th July 2019) - Grover, Charu; Bansal, Sangeeta
Abstract : Purpose: This paper aims to investigate the role of certification in providing information and reducing market inefficiencies when the "certification process is imperfect". In the setting, eco-labels imperfectly signal environmental product quality to consumers where the error in the process of certification could be either Type 1 or Type 2 error. The paper examines firms' incentive to get certified, equilibrium quantities and profits. The authors use perfect Bayesian equilibrium concept for the analysis. They then examine conditions for separating and pooling equilibrium to exist and welfare implications of certification process. Design/methodology/approach: The paper uses a vertical product differentiated model where firms are competing in quantities. Consumers are unable to observe the environmental quality of the product. To signal the product quality to consumers, firms may adopt certification by a third party. Using a framework where certification process is imperfect, the paper derives conditions for Perfect Bayesian separating and pooling equilibrium to exist. Findings: The paper shows that the existence of separating and pooling equilibrium depends on the certification fee. A separating equilibrium, where one firm seeks certification and other firm does not seek certification exists for an intermediate value of certification fee. A pooling equilibrium, where both firms seek certification, exists only when the certification fee is sufficiently small. The paper shows conditions for the certification fee for which welfare will be higher under separating equilibrium as compared to pooling equilibrium and analyses welfare implications for subsidy policy for the certification fee. Originality/value: The paper contributes to the literature by examining the role of labelling under imperfect certification.